Wafer-scale fabrication of fused silica chips for low-noise recording of resistive pulses through nanopores. (9th April 2019) - de Vreede, Lennart J; Ying, Cuifeng; Houghtaling, Jared; Figueiredo Da Silva, Jacqueline; Hall, Adam R; Lovera, Andrea; Mayer, Michael
Abstract: This paper presents a maskless method to manufacture fused silica chips for low-noise resistive-pulse sensing. The fabrication includes wafer-scale density modification of fused silica with a femtosecond-pulsed laser, low-pressure chemical vapor deposition (LPVCD) of silicon nitride (SiN x ) and accelerated chemical wet etching of the laser-exposed regions. This procedure leads to a freestanding SiN x window, which is permanently attached to a fused silica support chip and the resulting chips are robust towards Piranha cleaning at ∼80 °C. After parallel chip manufacturing, we created a single nanopore in each chip by focused helium-ion beam or by controlled breakdown. Compared to silicon chips, the resulting fused silica nanopore chips resulted in a four-fold improvement of both the signal-to-noise ratio and the capture rate for signals from the translocation of IgG1 proteins at a recording bandwidth of 50 kHz. At a bandwidth of ∼1 MHz, the noise from the fused silica nanopore chips was three- to six-fold reduced compared to silicon chips. In contrast to silicon chips, fused silica chips showed no laser-induced current noise—a significant benefit for experiments that strive to combine nanopore-based electrical and optical measurements.